Reoxygenation of the Hypoxia in the East China Sea: A Ventilation Opening for Marine Life - Chen, Chung-Chi; Ko, Dong S.; Gong, Gwo-Ching; Lien, Chun-Chi; Chou, Wen-Chen; Lee, Hung-Jen; Shiah, Fuh-Kwo; Huang, Yu-Sin Wita (Frontiers in Marine Science, 2022)
Hypoxia and upwelling co-occur in the summer, and well-mixed water typically reaches the subsurface in the East China Sea (ECS), especially off the Changjiang River estuary. The impact of upwelling on hypoxia and, therefore, on the ecosystem in the ECS is not known. This study demonstrates both positive and negative effects of upwelling on hypoxia and its impact on the ecosystem. With upwelling, the spatial extent of hypoxic water increases with a lower pH but waters with high regenerated nutrients and fugacity of CO2 (fCO2), which are normally confined to the near-bottom, are found just up to 5–10 m below the surface. This upwelled high nutrient water can enhance phytoplankton growth in this region. On one occasion in August 2014, upwelling reached to the surface and lasted for 3 weeks, with the area of coverage ranging from 326.8 to 24,368.0 km2. During this event, the water was mixed thoroughly throughout the water column, with high concentrations of nutrients, chlorophyll a, and slightly undersaturated dissolved oxygen but saturated fCO2, alongside a normal pH. This event may have served as an important pathway from the ocean to the atmosphere for the regenerated CO2. It also provided a productive and suitable environment for marine life and ventilation to alleviate low-oxygen stress in this hypoxic but upwelling region in the ECS.